2005
DOI: 10.1002/mus.20393
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of electrodiagnostic techniques in the evaluation of suspected tarsal tunnel syndrome: An evidence‐based review

Abstract: This evidence-based review was performed to evaluate the utility of nerve conduction studies (NCSs) and needle electromyography (EMG) in the diagnosis of tibial neuropathy at the ankle (tarsal tunnel syndrome, TTS). A total of 317 articles on TTS were identified that were published in English from 1965 through April 2002, from the National Library of Medicine MEDLINE database. All articles were reviewed on the basis of six selection criteria. The results of this search revealed that four articles met five or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 18 publications
0
67
0
5
Order By: Relevance
“…A literature review of the of Tarsal Tunnel evaluation techniques [7] confirmed a significant lack of standardization in methodology , and little regard for the variability and complex nature of the anatomy of the tibial nerve in suspected cases. This extensive review of 317 articles and studies on the topic confirmed that that needle EMG to the Adductor Halluces and the Adductor Digiti Quinti was never used in the assessment of TTS.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review of the of Tarsal Tunnel evaluation techniques [7] confirmed a significant lack of standardization in methodology , and little regard for the variability and complex nature of the anatomy of the tibial nerve in suspected cases. This extensive review of 317 articles and studies on the topic confirmed that that needle EMG to the Adductor Halluces and the Adductor Digiti Quinti was never used in the assessment of TTS.…”
Section: Discussionmentioning
confidence: 99%
“…67 There are many in the electrodiagnostic community who believe that findings of denervation in the intrinsic foot muscles are common in asymptomatic individuals; therefore, any needle electrode findings would be of little use. 68,69 Others, however, have disputed this claim. 70 A pattern of EMG abnormalities that would support the diagnosis includes denervation of intrinsic foot muscles isolated to the symptomatic limb of patients who have unilateral disease, with sparing of abnormalities of the extensor digitorum brevis (EDB).…”
Section: Tarsal Tunnel Syndromementioning
confidence: 93%
“…Üst ekstremitede yapılan elektrofizyolojik çalışmaların aksine, ayak deformitesi, deri değişiklikleri ve ödem gibi faktörler nedeniyle, alt ekstremitelerdeki çalışmalarda motor ve duyusal cevapları elde etmek zor olabilir. [11] Mann ve Baxter ise, ayakta ağrı ve parestezi, pozitif Tinel işareti ve pozitif elektrodiyagnostik çalışma üçlüsü mevcutsa, TTS tanısının konulmasını önermiştir. Bu algoritmaya göre, eğer bu üçlünün her üç bileşeni de varsa, hastada TTS vardır; eğer sadece iki bulgu varsa, hastada olası TTS vardır ve dikkatlice incelenmelidir.…”
Section: Fizik Muayeneunclassified
“…Özellikle erken evrelerde, normal motor cevaplar TTS'yi dışlayamaz; patoloji sadece duyu lifleri ile sınırlı olabilir. [11] Mikst motor ve duyusal sinir iletim çalışmaları, tek başına duyusal sinir iletim çalışmalarına göre, erken değişiklikleri saptamada daha duyarlıdır. Anormal duyu iletim hızı ve anormal lezyonu olan olgularda, cerrahi olmayan yöntemlerin herhangi bir anlamlı etkisi olmadığı saptanmıştır.…”
Section: Elektrodiyagnostik çAlışmalarunclassified